Effects of Hydrogen-rich Water on Cariogenic Bacteria - Zhibin Liu; Eungyung Kim; Su-Hyung Hong; Kirim Kim; Eun-Kyong Kim; Myoung-Ok Kim (Indian Journal of Dental Research)
Context: Some kinds of electrolysed water have been reported to exhibit antioxidant and bactericidal activity. However, studies on the effect of electrolysed hydrogen-rich water (EHW) with a neutral pH on cariogenic bacteria are limited. Aim: This study aimed to evaluate the feasibility of using EHW as a mouthwash by examining its various effects on cariogenic bacteria. Materials and Methods: To test the bactericidal and anti-biofilm formation effects of EHW on Streptococcus mutans and Streptococcus sobrinus, bacterial growth curves, colony-forming unit (CFU) counts, and crystal violet staining of biofilms were examined after exposing the bacterial pellets to EHW or tap water as a control for one minute. In addition, the expressions of glucosyltransferase and glucan-binding proteins encoding genes were examined using real-time PCR. Results: Bacterial growth and biofilm formation were inhibited, and the number of CFUs was significantly reduced in the EHW group compared to the control group. The expression of genes encoding glucosyltransferases (gtfB, gtfC, and gtfI) and glucan-binding proteins (gbpC and dblB) were also decreased in the EHW group compared to the control. Conclusions: Exposing cariogenic bacteria to EHW at neutral pH for one minute can effectively inhibit bacterial growth and biofilm formation in vitro, suggesting that EHW is a promising mouthwash.